THEORY OF CHROMOSOMES IN INHERITANCE - Odiljonov Yusufjon Farhodjonog’li; Kakhorova Karomatkhon Sovronbaevna, (Western European Studies, 2024)
Theory of Chromosomes in Inheritance discusses how chromosomes play a key role in passing traits from one generation to the next. Starting with early genetic studies by U.Betson and R.Punnett, it highlights Thomas Morgan’s experiments with fruit flies,which revealed that genes on the same chromosome are often inherited together, a concept known as genetic linkage.Theory of Chromosomes in Inheritance also explains crossovers - the exchange of genetic material between chromosomes during meiosis - that create genetic variation. This fundational theory connects classical genetics with the chromosomal basis of inheritance, offering insight into how traits are inherited and diversified.
Keywords: Linkage group; Crossover; Non-crossover